An Ecological Study on the Occurrence and Distribution of Aquatic Fungi in Sarchnar Water Spring within Sulaimani Province/ Kurdistan Region of Iraq - Farkha, Trifa K; Abdulrahman, Adiba S (Al-Nahrain Journal of Science, 2011)
Mycological and ecological studies have been carried out at four stations of Sarchnar water spring: (Sarchnar spring pools, Sarchnar district waste water, Chaq Chaq stream (industrial water) and confluence of these three stations, Selected within Sulaimani Governorate during April to August 2008.Certain physico-chemical parameters of water were perforormed using standard methods. The first investigation of total of twelve aquatic fungus species from 163 isolates was reported.Eleven species were identified in which 8 of them belonging to the family Saproleginaceae including, Achlya americana, A. apiculata, A. racemosa, Saprolegnia ferax, S. parasitica and S. litoralis and 2 species of Aphanomycese laevis and Aphanomycese stellates, three an identified species belonging to each of the familes Leptomitaceae, Pythiaceae and Blastocladiaceae which including Leptomitus sp, Pythium sp and Allomyces sp respectively, and one species of Chytrid which belongs to the class Chytridiomycota were recorded. Sarchnar spring pool was the richest station with aquatic fungus species, while Sarchnar district sewage water was the poorest station. Some physico-chemical parameters showing a significant relationship to the fungal occurrence and distributions.